2020
DOI: 10.1111/jphp.13225
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of breast cancer resistance protein and P-glycoprotein by ezrin, radixin and moesin in lung, intestinal and renal cancer cell lines

Abstract: Objectives Ezrin (Ezr), radixin (Rdx) and moesin (Msn) (ERM) proteins anchor other proteins to the cell membrane, serving to regulate their localization and function. Here, we examined whether ERM proteins functionally regulate breast cancer resistance protein (BCRP) and P‐glycoprotein in cell lines derived from lung, intestinal and renal cancers. Methods ERM proteins were each silenced with appropriate siRNA. BCRP and P‐gp functions were evaluated by means of efflux and uptake assays using 7‐ethyl‐10‐hydroxyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…ERM proteins bind to integral membrane proteins, scaffold proteins, and Rho-related proteins (Table 1) [57]. It was recently established that ERM proteins act as scaffolds to anchor efflux transporters to the cell membrane, thereby regulating the functional activity [36]. Luciani et al found that treatment of macrophages with interferon γ increased the expression of P-gp on the cell membrane and its co-localization with Ezr among ERM proteins.…”
Section: Relationship Between Erm Scaffold Proteins and Efflux Transpmentioning
confidence: 99%
See 3 more Smart Citations
“…ERM proteins bind to integral membrane proteins, scaffold proteins, and Rho-related proteins (Table 1) [57]. It was recently established that ERM proteins act as scaffolds to anchor efflux transporters to the cell membrane, thereby regulating the functional activity [36]. Luciani et al found that treatment of macrophages with interferon γ increased the expression of P-gp on the cell membrane and its co-localization with Ezr among ERM proteins.…”
Section: Relationship Between Erm Scaffold Proteins and Efflux Transpmentioning
confidence: 99%
“…We also investigated whether ERM proteins functionally regulate P-gp in non-small cell lung cancer HCC827 cells [36]. In HCC827 cells, Ezr or Msn knockdown significantly reduced the Rho123 efflux rate.…”
Section: Relationship Between Erm Scaffold Proteins and Efflux Transpmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies reported that the most common cause of MDR is the abnormally high expression of ATP-binding cassette (ABC) transporters in leukemia cells (6,7). In fact, it was shown that the overexpression of ABCB1, ABCC1 and ABCG2 was involved in the efflux of various antitumor agents out of the cells (8). These proteins have the ability to transport a plethora of chemotherapeutics with diverse structures and functions outside of the cells.…”
Section: Introductionmentioning
confidence: 99%